Geographic and Orientia infection status influence on the bacterial microbiome of free-living chiggers in North Carolina, USA - Kaiying Chen; Nicholas V. Travanty; Reuben A. Garshong; Gideon Wasserberg; Charles S. Apperson; R. Michael Roe; Loganathan Ponnusamy (PLoS ONE, 2026)
Chiggers (larval Trombiculid mites) serve as vectors for Orientia species that cause scrub typhus, a potentially serious illness in humans with a broadening global distribution. To date, there is limited research on the chigger microbiome in the United States (US) compared to some other parts of the world. Investigating chigger bacterial communities is essential for understanding the potential role they play in pathogen transmission dynamics within these arthropods. This study investigated the bacterial communities of free-living chiggers collected from sites across the three ecoregions in North Carolina using 16S rDNA gene targeted next-generation sequencing. Molecular identification of the chigger revealed three species: Eutrombicula splendens , Eutrombicula tinami , and Pseudoschoengastia sp. All three trombiculid mite species occurred at least once in the Mountains and Piedmont, except for E. tinami , which was absent from the Coastal Plain ecoregion. Microbiome analysis revealed significant differences in alpha and beta diversity among the collection sites for E. splendens . No significant differences in overall microbiome diversity were observed between E. splendens and Pseudoschoengastia sp., the two dominant chigger species. However, the microbiome of E. splendens alone exhibited significant differences in both Shannon diversity and beta diversity between Orientia -infected and uninfected individuals. Within E. splendens , genera like Brevibacillus and Telluria were more abundant in Orientia -positive chiggers, while Methylobacterium was more abundant in Orientia -negative chiggers. We also found potentially pathogenic bacterial genera, including Rickettsia , Listeria , Legionella , Staphylococcus , and Streptococcus sequences. These findings suggest that geography and Orientia infection influence chigger-associated bacterial communities, potentially affecting their vector competence.